What Impinges the Choice of Cell Phone Connection? - Dhanda, Neelaam; Goel, Pooja (Indian Journal of Marketing, 2010)
Telecommunications, being one of the prime support services is required not only for rapid growth, but also for the modernization of various sectors of the economy. It has become especially important in recent years because of enormous growth of Information Technology (IT) and its linkage to the other sectors. Long back, the telecom network in India was owned and managed by government as it is considered as a strategic service. During that time, the telecom industry had a monopoly. Liberalization made the Government to adopt a gradual approach for the telecom sector reforms. Through selective privatization, competition was managed in different segments of the telecom market. In 1992, India introduced private competition in value-added services followed by opening up of the cellular and basic services for local area to private competition. The Telecom Regulatory Authority of India (TRAI) was constituted in 1997 as an independent regulator in this sector. With an addition of more than 6 million connections per month, India has become one of the fastest growing telecom markets in the world. The expanding spectrum and enormous growth have made the cellular operations highly competitive. Although the network in rural areas is expanding, but still the rural areas are not adequately covered. India is the 4th largest telecom market in Asia after China, Japan and South Korea. India is the 5th largest telecom market in the world and 2nd largest among emerging economies of Asia. Contribution of telecom sector in terms of revenue is 2.1 percent of the GDP as compared to 2.8 percent in developed economies.